The Handless Maiden : Moriscos and the Politics of Religion in Early Modern Spain. - Perry, Mary Elizabeth (Jews, Christians, and Muslims from the ancient to the modern world., 2013)
In 1502, a decade of increasing tension between Muslims and Christians in Spain culminated in a royal decree that Muslims in Castile wanting to remain had to convert to Christianity. Mary Elizabeth Perry uses this event as the starting point for a remarkable exploration of how Moriscos, converted Muslims and their descendants, responded to their increasing disempowerment in sixteenth- and early-seventeenth-century Spain. Stepping beyond traditional histories that have emphasized armed conflict from the view of victors, The Handless Maiden focuses on Morisco women. Perry argues that t.